2006
DOI: 10.1523/jneurosci.2815-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Cre Expression in Neuronal Progenitors Cause Defects in Brain Development Leading to Microencephaly and Hydrocephaly

Abstract: Hydrocephalus is a common and variegated pathology often emerging in newborn children after genotoxic insults during pregnancy (Hicks and D'Amato, 1980). Cre recombinase is known to have possible toxic effects that can compromise normal cell cycle and survival. Here we show, by using three independent nestin Cre transgenic lines, that high levels of Cre recombinase expression into the nucleus of neuronal progenitors can compromise normal brain development. The transgenics analyzed are the nestin Cre Balancer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
126
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 47 publications
(62 reference statements)
8
126
1
1
Order By: Relevance
“…In the latter study, the genotoxic effects required the levels of Cre recombinase to reach a critical, high threshold in the cell nucleus, as had been reported previously in vitro (Baba et al, 2005). Thus, hydrocephalus was observed in homozygous, but not hemizygous, mice in a transgenic line, in which multiple copies of the cre transgene had been inserted into unknown locations in the genome (Forni et al, 2006). In contrast, the present study utilized a Foxg1-cre line that has only a single copy of the cre gene and effects of Cre recombinase at low doses in vivo have not been reported previously.…”
Section: Effects Of Cre Recombinasesupporting
confidence: 61%
See 4 more Smart Citations
“…In the latter study, the genotoxic effects required the levels of Cre recombinase to reach a critical, high threshold in the cell nucleus, as had been reported previously in vitro (Baba et al, 2005). Thus, hydrocephalus was observed in homozygous, but not hemizygous, mice in a transgenic line, in which multiple copies of the cre transgene had been inserted into unknown locations in the genome (Forni et al, 2006). In contrast, the present study utilized a Foxg1-cre line that has only a single copy of the cre gene and effects of Cre recombinase at low doses in vivo have not been reported previously.…”
Section: Effects Of Cre Recombinasesupporting
confidence: 61%
“…More detailed analysis indicated that proliferating, rather than postmitotic, cells were vulnerable to the effects of Cre recombinase, as cryptic recombination events were only observed in mitotically-active cells (Loonstra et al, 2001). There have been two reports of overt pathology in cre-expressing transgenic mice, where high levels of Cre resulted in male infertility when expressed in postmeiotic spermatids (Schmidt et al, 2000) and hydrocephaly when expressed in neuronal progenitors (Forni et al, 2006). In the latter study, the genotoxic effects required the levels of Cre recombinase to reach a critical, high threshold in the cell nucleus, as had been reported previously in vitro (Baba et al, 2005).…”
Section: Effects Of Cre Recombinasementioning
confidence: 53%
See 3 more Smart Citations